Child dietary patterns in Homo sapiens evolution: A systematic review. Issue 1 (26th July 2022) - Iannotti, Lora L; Gyimah, Emmanuel A; Reid, Miranda; Chapnick, Melissa; Cartmill, Mary Kate; Lutter, Chessa K; Hilton, Charles; Gildner, Theresa E; Quinn, Elizabeth A
Abstract: Dietary patterns spanning millennia could inform contemporary public health nutrition. Children are largely absent from evidence describing diets throughout human evolution, despite prevalent malnutrition today signaling a potential genome-environment divergence. This systematic review aimed to identify dietary patterns of children ages 6 months to 10 years consumed before the widespread adoption of agriculture. Metrics of mention frequency (counts of food types reported) and food groups (globally standardized categories) were applied to: compare diets across subsistence modes [gatherer–hunter–fisher (GHF), early agriculture (EA) groups]; examine diet quality and diversity; and characterize differences by life course phase and environmental context defined using Köppen–Geiger climate zones. The review yielded child diet information from 95 cultural groups (52 from GHF; 43 from EA/mixed subsistence groups). Animal foods (terrestrial and aquatic) were the most frequently mentioned food groups in dietary patterns across subsistence modes, though at higher frequencies in GHF than in EA. A broad range of fruits, vegetables, roots and tubers were more common in GHF, while children from EA groups consumed more cereals than GHF, associated with poor health consequences as reported in some studies. Forty-eight studies compared diets across life course phases: 28 showed differences and 20 demonstrated similarities in child versus adult diets. Climate zone was a driver of food patterns provisioned from local ecosystems. Evidence from Homo sapiens evolution points to the need for nutrient-dense foods with high quality proteins and greater variety within and across food groups. Public health solutions could integrate these findings into food-based dietary guidelines for children. Lay Summary: Drawing insights from child dietary patterns of our evolutionary past might better inform public health nutrition today. This systematic review revealed higher intakes of animal source foods (ASF), fruits, roots/tubers, nuts and overall dietary diversity among gather–hunter–fisher compared to early agriculture groups. To prevent child malnutrition, dietary guidelines might incorporate these findings.